Comparative Study on the Preparation and Characterization of Starch Nanoparticles from Corn, Potato, and Wheat Starch - Shilpa Thakur; Dr. Dharmendra Ahuja; Dr. Anamika Verma (Revista Electronica de Veterinaria, 2024)
Nanotechnology has paved the path for enhanced biomedical applications, particularly novel drug delivery systems. Starch nanoparticles, among other nanomaterials, have emerged as a viable platform due to intrinsic benefits such as biodegradability, biocompatibility, and non-toxicity. Nanoprecipitation, a well-known approach for preparing stable nanostructures, was used to create the nanoparticles. To guarantee reproducibility and the intended physicochemical qualities, critical formulation factors as starch concentration, surfactant content, and stirring speed were optimized. The properties of potato starch nanoparticles were better than those of corn and wheat. They showed greater homogeneity with a reduced polydispersity index (PDI) and a more uniform distribution, with an average particle size of about 140 nm. The zeta potential of the nanoparticles was -25 mV, indicating improved colloidal stability. Their robustness was further validated by thermal and pH stability investigations, which makes them appropriate for biological applications that need stability in physiological conditions. The results highlight potato starch’s potential as an ideal candidate for systems based on nanoparticles, especially in drug delivery applications where stability, homogeneity of size, and biodegradability are essential. This work establishes the foundation for further investigations into the functionalization and usage of potato starch nanoparticles in certain therapeutic and diagnostic platforms.